Molecular Pathway of Phytochemicals in Preventing Sarcopenia - Sari, Desy Nofita; Goenarjo, Roman Ardian; Sianipar, Imelda Rosalyn (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
Sarcopenia, the age-related decline in muscle mass and function, poses a significant global health challenge. This systematic review synthesizes evidence from preclinical studies published between 2020 and 2025 to elucidate the molecular pathways through which phytochemicals prevent sarcopenia. Following PRISMA guidelines, a systematic search of databases identified 16 eligible studies. The analysis reveals that phytochemicals, including flavonoids, polyphenols, and botanical extracts, mitigate muscle atrophy by concurrently enhancing anabolic signaling via the IGF-1/PI3K/Akt/mTOR axis, suppressing proteolysis, improving mitochondrial biogenesis, and reducing oxidative stress and inflammation. Notably, combinatorial formulations and multi-target extracts demonstrate superior efficacy. The review concludes that phytochemicals represent a promising multi-targeted strategy against sarcopenia; however, this promising potential necessitates future validation through standardized clinical trials to establish efficacy and safety in human populations.